Mycorrhizal Fungi Modulate the Development and Composition of Purslane (Portulaca oleracea L.) Bioactive Compounds - Marieta Hristozkova; Katrin Valkova; Maria Geneva (Agriculture, 2025)
The present research focused on the physiological alterations and antioxidant potential of Portulaca oleracea L. due to mycorrhizal symbiosis with diverse strains. Purslane belongs to the plants that form a symbiosis with mycorrhizal fungi and show tolerance to various strains. Inoculation with Funneliformis mosseae gave better mycorrhizal colonization results and positively affected biomass accumulation and the concentration of reducing sugars. The total accumulation of plastid pigments was higher in symbiotic plants, although this effect was not specific to any particular strain. Mycorrhizal fungi increased the levels of carotenes in the shoots, while xanthophylls decreased, with the highest values observed in non-inoculated plants. Both strains influenced the ratio of betalains: Funneliformis mosseae promoted the accumulation of β-cyanins, while Claroideoglomus claroideum increased β-xanthines. The association with Funneliformis mosseae also affected antioxidant capacity, as indicated by the FRAP test, by altering the concentrations of secondary metabolites, particularly phenols and flavonoids. Targeted inoculation with specific strains boosts both non-enzymatic (including water-soluble and lipid-soluble metabolites) and enzymatic antioxidant activity; however, it was not dependent on the strain. These findings underscore the benefits of mycorrhizal associations in purslane cultivation, promoting sustainable ecological practices and enhancing its quality as a food product.